1998
DOI: 10.1159/000018629
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Locally Advanced Rectal Cancer

Abstract: Aims: The results of surgical treatment of locally advanced rectal cancer with special regard to multivisceral resections and preoperative radiotherapy should be analyzed. Methods: From 10/86 until 12/95, 40 patients with preoperatively assessed T4 stage rectal cancer were treated in our department whose data were evaluated retrospectively. Results: Apart from 10 nonresecting procedures we performed 30 resections in which the mortality rate was 7%. In 50% of these patients a multivisceral resection was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
1
12
0
3
Order By: Relevance
“…28 The average rate of pathologic invasion to the organs of combined resection was 54 percent, with a range of 25 percent to 84 percent in patients who had received multivisceral resection for colorectal cancer in the previous series. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The local recurrence rate was much higher when adherent organs were separated from the tumor than when en bloc resection was performed (69 percent vs. 18 percent). 7 The five-year survival rate was 17 percent after inadvertent dissection or rupturing of the tumor, compared with 49 percent after en bloc resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 The average rate of pathologic invasion to the organs of combined resection was 54 percent, with a range of 25 percent to 84 percent in patients who had received multivisceral resection for colorectal cancer in the previous series. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The local recurrence rate was much higher when adherent organs were separated from the tumor than when en bloc resection was performed (69 percent vs. 18 percent). 7 The five-year survival rate was 17 percent after inadvertent dissection or rupturing of the tumor, compared with 49 percent after en bloc resection.…”
Section: Discussionmentioning
confidence: 99%
“…[Key words: Multivisceral resection; Colorectal cancer; Postoperative complication; Morbidity and mortality; Prognostic factors; Blood transfusion] M ultivisceral resection is sometimes required to cure locally advanced colorectal cancer. 1 Many investigators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have reported that multivisceral resection for colorectal cancer has shown acceptable morbidity and mortality rates and has a fair long-term prognosis, and have thus emphasized the benefits of this procedure. However, it is also well recognized that a highly extended operation increases morbidity and mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a situation may demand different operative strategies and technical skills from the surgical team (2,17) . Within this context, a proper oncologic approach includes an en-bloc multivisceral resection of all organs and/or structures involved.…”
Section: Introductionmentioning
confidence: 99%
“…Mit diesem Ziel konnte die Resektionsrate bei primär nicht resektablen Rektumkarzinomen nach kombinierter präoperativer Radiochemotherapie auf bis zu 90% angehoben werden, ohne hierbei die perioperative Morbidität wesentlich zu erhöhen [1,13,24].…”
unclassified